Proceedings of an emergency medical team (paramedics) with a patient in anaphylaxis - Babuśka Roczniak, Magdalena; Wojtanowska Kaczka, Magdalena; Racz, Oliver; Marek, Hubert; Sośnicki, Krzysztof; Roczniak, Wojciech (Journal of Education, Health and Sport, 2020)
Introduction: Anaphylactic shock is an acute allergic body reaction to allergens. This condition threatens the patient's life and health. Anaphylaxis can be caused by intolerance to many nutrients, medications or hymenoptera stings. Aim of the manuscript: The aim of the manuscript was to determine the pattern of proceedings of emergency medical teams with patients in anaphylactic shock. Material and methods: The individual case method of a patient stung by a Hymenoptera insect, for whom a medical rescue team was dispatched, was used. The research material was obtained thanks to the analysis of medical rescue operations and dispatch orders. Results: The analysis of medical records of the injured person depicted an appropriate algorithm of proceedings with a patient in anaphylactic shock. In anaphylaxis, it is important to gather information as soon as possible, make an accurate and prompt diagnosis, and provide immediate pharmacotherapy. In this case, the first-line drug is Adrenaline, which prevents the release of histamine and reverses the effects of shock. Further treatment requires oxygen, fluids and second-line pharmacotherapy. Conclusions: The emergency medical team followed the applicable algorithms and current knowledge. It implemented appropriate medical rescue operations, thanks to which the condition of the injured was stabilized. The first step is to stop the exposure to the allergen.